Healthcare Workers and Nonhealthcare Workers Pro-Vaccination Attitude and Its Associated Factors towards COVID-19 Vaccine Globally: A Systematic Review and Meta-Analysis - Wake, Addisu Dabi (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Introduction. Coronavirus disease 2019 (COVID-19) pandemic has not been managed and controlled globally. The aim of this systematic review and meta-analysis were to determine the global pro-vaccination attitude and associated factors towards COVID-19 vaccine among healthcare workers (HCWs) and nonhealthcare workers (non-HCWs). Methods. Different databases such as PubMed, Scopus, EMBASE, and Google Scholar were used. Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 flowchart diagram and PRISMA checklist were used for study screening, selection, and inclusion into this systematic review and meta-analysis. Newcastle-Ottawa Scale (NOS) quality assessment criteria for cross-sectional studies were used to assess the included articles. Results. A total of 51 studies were included into this systematic review and meta-analysis. The meta-analysis revealed that the global pooled prevalence of pro-vaccination attitude towards COVID-19 vaccine among both HCWs and non-HCWs was 61.30% (95%CI: 56.12, 66.47, I2 = 99.8%: p=0.000). Subgroup analysis showed that the global pooled prevalence of pro-vaccination attitude towards COVID-19 vaccine was the lowest (59.77%, 95%CI (51.56, 67.98); I2 = 99.6%, p=0.000) among the HCWs participants and the highest (62.53%, 95%CI (55.39, 69.67); I2 = 99.8%, p=0.000) among the non-HCWs participants and the lowest (54.31%, 95%CI (43, 65.63); I2 = 99.5%, p=0.000) for sample size <700 and the highest (66.49%, 95%CI (60.01, 72.98); I2 = 99.8%, p=0.000) for sample size >700; the lowest (60.70%, 95%CI (54.08, 67.44); I2 = 93.0%, p=0.000) for studies published in 2020 year and the highest (61.31%, 95%CI (55.93, 66.70); I2 = 99.8%, p=0.000) for the studies published after 2020 years. From this systematic review, factors significantly associated with pro-vaccination attitude towards COVID-19 vaccine among HCWs were such as age, gender, race, work experience, home location, having no fear of injections, being a non-smoker, profession, presence of chronic illnesses, allergies, confidence in pharmaceutical companies, history of taking influenza vaccine, vaccine recommendation, perceived risk of new vaccines, perceived utility of vaccine, receiving a seasonal flu vaccination in the last 5 years, working in a private hospital, a high perceived pandemic risk index, low vaccine harm index, high pro-socialness index, being in close contact with a high-risk group, knowledge about the virus, confidence in and expectations about personal protective equipment, and behaviors. The level of positive attitude towards COVID-19 vaccine among non-HCWs ranged from 21.40% to 91.99%. Factors associated with the attitude towards COVID-19 vaccine among non-HCWs were such as age, gender, educational level, occupation, marital status, residency, income, ethnicity, risk for severe course of COVID-19, direct contact with COVID-19 at work, being a health profession, being vaccinated against seasonal flu, perceived benefits, cues to actions, having previous history of vaccination, fear of passing on the disease to relatives, and the year of medical study, studying health-related courses, COVID-19 concern, adherence level to social distancing guidelines, history of chronic disease, being pregnant, perceived vaccine safety, having more information about vaccine effectiveness, mandatory vaccination, being recommended to be vaccinated, lack of confidence in the healthcare system to control epidemic, and belief in COVID-19 vaccines protection from COVID-19 infection. Conclusion. This meta-analysis revealed that the global estimated pooled prevalence of pro-vaccination attitude towards COVID-19 vaccine among both HCWs and non-HCWs was unsatisfactory. Globally, there is a need for a call for action to cease the crisis of this pandemic.